Study on kinetics and bio-oil production from rice husk, rice straw, bamboo, sugarcane bagasse and neem bark in a fixed-bed pyrolysis process. (1st January 2020) - Gautam, Neha; Chaurasia, Ashish
Abstract: In this study, rice husk, rice straw, bamboo, sugarcane bagasse, and neem bark were pyrolyzed in a fixed-bed pyrolyzer to examine the influence of operating conditions, such as the temperature of the pyrolysis process, residence time of volatiles, and reactor length, on the yield of bio-oil and individual gas components. The temperature of pyrolysis was varied from 350 to 650 °C at increments of 50 °C, and the length of the reactor was varied from 45 to 60 cm at intervals of 5 cm. The maximum bio-oil production of 46.93 wt% and the pyrolysis char of 26.2 wt% was obtained for bamboo at 450 °C. The highest amount of clean syngas (carbon monoxide and hydrogen) was produced for neem bark (52.61 vol%). The gaussian distributed activation energy model data exhibited a superior fit with the experimental data compared with the single-reaction model for bio-oil and all other individual component gases. The presence of C–H, CC, alcohols and phenolic compounds indicated that the bio-oil obtained from all the biomass species could potentially be used as fuel. The steady-state mass and energy balances for the entire pyrolysis plant were obtained using the Aspen Plus simulation. Highlights: Bamboo exhibited maximum bio-oil and net char production of 46.93 and 26.2 wt%. Neem bark, rice husk and straw have syngas production of 52.6, 52.2 and 51.9 vol%. Phenolic compounds and alcohols in these bio-oils show its potential as a bio-fuel. The gaussian DAEM data exhibited a superior fit to the experimental data. Mass and energy balances for the entire pyrolysis plant were obtained using Aspen.